تاثير ممارسات القيادة الأخلاقية في إدارة الموارد البشرية على الولاء التنظيمي بالمركز الاستشفائي الجامعي Chu بوهران - بوطيبة, مختارية (جامعة الوادي - University of Eloued, 2022)
سلطت هذه الدراسة الضوء على تحليل العلاقة التاثيرية بين ممارسات القيادة الأخلاقية على مستوى إدارة الموارد البشرية و الولاء التنظيمي ، من خلال دراسة دور العدالة التنظيمية بابعادها الثلاث : التوزيعية ، الإجرائية و التقييمية في تعزيز الولاء التنظيمي لدى موظفي المركز الاستشفائي الجامعي بوهران ، و لهذا الغرض تم استهداف عينة مكونة من 40 موظف للإجابة على استبانة الدراسة ، و التي تم تحليل معطياتها باستخدام /v21) (SPSS و (smart PLS/v3) لاختبار الاتساق العام للاستبانة ، التحليل الاحصائي لمحاورها ، واختبار فرضيات الدراسة. تشير نتائج دراستنا الى وجود علاقة ارتباطية تاثيرية بين ممارسات القيادة الأخلاقية على مستوى إدارة الموارد البشرية و العدالة التنظيمية ، في حين لا تؤثر هذه الأخيرة في تعزيز الولاء التنظيمي لدى موظفي المركز الاستشفائي. : This study sheds light on the analysis of the influence relationship between ethical leadership practices at the level of human resource management and organizational loyalty, by studying the role of organizational justice in its three dimensions: distributive, procedural and evaluative in enhancing organizational loyalty among the employees of the University Hospital Center in Oran. Targeting a sample of 40 employees to answer the study questionnaire, the data of which were analyzed using (SPSS /v21) and (smart PLS/v3) to test the general consistency of the questionnaire, the statistical analysis of its axes, and to test the study hypotheses.The results of our study indicate that there is an effective correlation between ethical leadership practices at the level of human resource management and organizational justice, while the latter does not affect the enhancement of organizational loyalty among the employees of the Hospital center
The impact of ethical leadership practices in human resource management on organizational loyalty at the University Hospital Center CHU - Ora
مقال
Keywords: إدارة الموارد البشرية ; القيادة الاخلاقية ; العدالة التنظيمية ; الولاء التنظيمي